NON-PHARMACOLOGICAL THERAPY FOR CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD): A SYSTEMATIC REVIEW - Imam, Nurul; Darmawan, Taufan Citra; Alfianti, Khalifatus Zuhriyah; Aga, Maria Sofia Anita; Dianita, Eka Mei; Fernanda, Pradita Ayu; Rusmeni, Ni Putu Diah Ayu (Nurse and Holistic Care, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death worldwide. This disease attacks the respiratory tract, resulting in chronic symptoms such as narrowing of the airways, shortness of breath, and coughing. However, the management of treatment for this disease is still very lacking. Therefore, the best treatment needs to be understood. Objective: This review article aims to explain the best treatment for COPD sufferers. Design: This study employed a systematic review design guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Data Sources: A comprehensive literature search was conducted using four electronic databases—Scopus, PubMed, Science Direct, and Google Scholar—focusing on articles published between 2020 and 2025. Keywords used included "Non-Pharmacology", "COPD", "Chronic Obstructive Pulmonary Disease", "Therapy", "Intervention", and "Nursing". Studies were included if they used Pre-Experimental, Quasi-Experimental, Randomized Controlled Trial, or Qualitative research designs. Review Methods: Two reviewers performed data extraction and risk of bias assessment independently using the Joanna Briggs Institute (JBI) checklist, with discrepancies resolved through consensus or a third reviewer. Results: A review of 19 articles showed that non-pharmacological interventions, such as telerehabilitation, physical exercise, and breathing techniques, have been shown to help improve the functional capacity and quality of life of COPD patients. Conclusions: The combination of physical and psychological therapies has shown more optimal results, especially with the support of technology. However, further research is needed to evaluate long-term effectiveness and ensure wider and more targeted implementation.